2005
DOI: 10.2174/092986705774462914
|View full text |Cite
|
Sign up to set email alerts
|

MAP Kinase p38Inhibitors: Clinical Results and an Intimate Look at Their Interactions with p38α Protein

Abstract: Mitogen-activated protein kinase p38 is a serine/threonine kinase originally isolated from lipopolysaccharide (LPS) stimulated monocytes. There are four isoforms p38alpha p38beta, p38gamma, and p38delta. The most thoroughly studied isoform is p38alpha, whose activation has been observed in many hematopoietic and non-hematopoietic cell types upon appropriate stimuli. Subsequently, p38alpha kinase has been shown to be involved in the biosynthesis of TNFalpha and IL-1beta at the translational and transcriptional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
172
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(179 citation statements)
references
References 29 publications
3
172
0
3
Order By: Relevance
“…Several compounds are in trials targeting p38 MAPK also in cardiovascular diseases, such as acute coronary syndrome (ACS) and inflammatory cardiovascular disorders. For example, a p38 inhibitor SB618323 is developed for treatment of coronary heart disease, and another inhibitor VX-702 is being studied in the treatment of ACS (Lee and Dominguez, 2005;Ding, 2006). Our present results highlight that more information about differences between the distinct p38 isoforms is needed to determine whether the pharmacological manipulation of p38 is useful in the treatment of cardiovascular and other diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Several compounds are in trials targeting p38 MAPK also in cardiovascular diseases, such as acute coronary syndrome (ACS) and inflammatory cardiovascular disorders. For example, a p38 inhibitor SB618323 is developed for treatment of coronary heart disease, and another inhibitor VX-702 is being studied in the treatment of ACS (Lee and Dominguez, 2005;Ding, 2006). Our present results highlight that more information about differences between the distinct p38 isoforms is needed to determine whether the pharmacological manipulation of p38 is useful in the treatment of cardiovascular and other diseases.…”
Section: Discussionmentioning
confidence: 99%
“…P38 belongs to a family of serine/threonine protein kinases with four different isoforms, of which the α isoform is the most studied [ 19 ]. It was first discovered in Finkelstein et al Page 5 monocytes, where it was noted to be phosphorylated and activated by LPS [ 4 ]. In a positive feedback loop, p38 regulates expression of cytokines and is also activated in immune cells by cytokines [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have demonstrated that p38 MAPK inhibitors improve survival in sepsis [ 7 -9 ]. In addition, p38 inhibitors have been shown to decrease TNF-α in human whole blood stimulated by LPS, and also decrease TNF-α stimulation of other inflammatory cytokines such as IL-1β and IL-6 [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…To study whether gp120-mediated p38 activation is a necessary event for gp120-induced CD4 T cell death, we used the specific p38 inhibitor, SB203580 (39). As shown in Fig.…”
Section: Gp120 Induces Cell Death Of Human Primary Cd4 T Cells In P38mentioning
confidence: 99%